Genetic insights into gut microbiota and risk of prostatitis: a Mendelian randomization study - Qin, Pengfei; He, Yanmei; Shao, Huan; Jiang, Dawei (Frontiers in Microbiology, 2024)
Background: The dysbiosis of gut microbiota (GM) is considered a contributing factor to prostatitis, yet the causality remains incompletely understood.The genome-wide association study (GWAS) data for GM and prostatitis were sourced from MiBioGen and FinnGen R10, respectively. In the two-sample Mendelian randomization (MR) analysis, inverse variance weighting (IVW), MR-Egger, weighted median, simple mode, weighted mode, and maximum likelihood (ML) methods were utilized to investigate the causal relationship between GM and prostatitis. A series of sensitivity analysis were conducted to confirm the robustness of the main results obtained from the MR analysis. Results: According to the IVW results, genus Sutterella (OR: 1.37, 95% CI: 1.09-1.71, p=0.006) and genus Holdemania (OR: 1.21, 95% CI: 1.02-1.43, p=0.028) were associated with an increased risk of prostatitis. The phylum Verrucomicrobia (OR: 0.76, 95% CI: 0.58-0.98, p=0.033) and genus Parasutterella (OR: 0.84, 95% CI: 0.70-1.00, p=0.045) exhibited a negative association with prostatitis, indicating a potential protective effect. Sensitivity analysis showed that these results were not affected by heterogeneity and horizontal pleiotropy. Furthermore, the majority of statistical methods yielded results consistent with those of the IVW analysis. Conclusions: In this study, we identified two GM taxon that might be protective against prostatitis and two GM taxon that could increase the risk of developing prostatitis. These findings could potentially provide a valuable theoretical basis for the future development of preventive and therapeutic strategies for prostatitis.